Pelatihan Branding dan Digital Marketing pada Umkm di Desa Dibal - Fahman Hadi Utomo; llham Karin Rizkiawan; Dwi Kharisma Wati (Pusat Riset dan Inovasi Nasional, 2023)
Efforts to improve the quality of Human Resources for the main actors/SMEs business actors in the form of changes in behavior both knowledge, attitudes and skills, cannot be done in an instant, but are long life education. Changes in the position of the main actors from message recipients and users technology becomes an active partner in Devotion activities for the development of its technology and business dissemination network. To answer the above problems, professional and competent extension workers are needed in their fields who are able to provide excellent service, one of which is through a model extension pilot unit at the field level based on recommended technology as an entrepreneurial activity for extension groups. In this regard, it is very necessary to conduct counseling on the Development of Processing, Packaging, Branding and Marketing of Tempe Products in the framework of Pilot Technology Development/Entrepreneurship Development of processed tempe products in Dibal Ngemplak Boyolali Village.